Benteng Rotterdam: Alih Fungsi Benteng Rotterdam Pasca Perjanjian Bongaya - Sri Rezky Meiliana, Sri Rezky Meiliana; Mastanning; Syukur, Syamzan (Universitas Islam Negeri Alauddin Makassar, 2023)
This research discusses the function of Fort Rotterdam which has changed several times, starting from Fort Rotterdam as a defense base which is the main function of the establishment of a fort especially during the kingdoms, to the fort which has changed and added functions tailored to the needs and interests of certain control. The results of this study indicate that the function of Fort Rotterdam experienced a transition and addition of functions in each period of control starting from the control of the Kingdom of Gowa, after the Bongaya agreement the fort was under the control of the Dutch, Japanese to the time after independence.